A study of serum sodium and potassium levels in subjects of acute myocardial infarction in a tertiary care hospital in Eastern India - Das, Siladitya; Saha, Satyendra Nath (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Cardiovascular disease is one of the most common causes of morbidity and mortality around the world. In countries like India, there is difference in the lifestyle and behavioural risk factors among different areas. There is existence of rural-urban, Eastern-Western-Northern-Southern zonal differences. Studies done in other parts of India may not completely be applicable to Eastern Indian population. Serum electrolytes play an important role in maintaining electrophysiological homeostasis of the myocardial membrane, and alterations of these electrolyte levels can affect the pathogenesis, complications of myocardial infarction. Major serum electrolytes affecting the myocardial electrophysiological properties are sodium, potassium. Hence, this study was undertaken keeping in mind the miniscule lacunae in current knowledge especially pertaining to diseases in Eastern Indian population. Methods: 50 consecutive patients in the age group of 30-70 years admitted in the medicine department of Burdwan medical college with recent onset acute chest pain, diagnosed to be acute myocardial infarction were taken, their serum sodium, potassium levels were determined and these levels were compared among these patients with and without risk factors. Results: Serum sodium was decreased among patients with history of smoking, hypertension, BMI ≥25, complicated by atrial fibrillations. Serum potassium was decreased in patients with hypertension, BMI ≥25, ventricular premature complexes and increased in smokers, alcoholics. Conclusions: Electrolyte imbalances are common in patients of Acute Myocardial Infarction. Hypokalemia and hyponatremia were present and they were associated with cardiac complications. They adversely affect prognosis, so should be corrected.